Optimalisasi Pertumbuhan dan Kualitas Buah Pepaya California (Carica pepaya L.) melalui Kombinasi Vermikompos dan Bakteri Fotosintesis - Yovi Avianto; Alan Handru (Jurnal Galung Tropika, 2026)
California pepaya is a highly popular fruit among Indonesian consumers. However, its productivity is often hindered by declining soil fertility caused by excessive use of chemical fertilizers. Substituting chemical fertilizers with vermicompost and photosynthetic bacteria has been reported to effectively improve soil fertility and enhance plant resilience. This study aims to optimize the growth and fruit quality of California pepaya through the combination of vermicompost and photosynthetic bacteria. The research was conducted from August 2023 to November 2024 at the Education and Research Farm (KP2) of the STIPER Agricultural Institute, Yogyakarta. The treatments tested in this study included vermicompost and the photosynthetic bacterium Rhodopseudomonas palustris, applied to planting holes, along with a control. Data on soil physical and chemical properties, as well as pepaya growth and production, were analyzed using an independent t-test, and their relationships were evaluated through correlation analysis. The results showed that the application of vermicompost and photosynthetic bacteria significantly improved soil physical properties of water-holding capacity. Vermicompost and photosynthetic bacteria also enhanced soil organik matter, C-organik, cation exchange capacity (CEC), and the availability of nutrients (N and K) while reducing chloride (Cl) levels. The combination of vermicompost and photosynthetic bacteria improved physiological parameters of pepaya plants, such as relative water content, and increased plant height, number of flower, and fruit brix levels, although fruit weight and length decreased.